Analysis of 16S rRNA for identification of new bacteria - Nurhayati Nurhayati (Universitas Muhammadiyah Semarang, 2018)
The major problem associated with bacteria classification, identification and identification is due to alack of data and methods. Correct data is crucial for the nomenclature of bacteria. Bacteria in thisregard, molecular approach is advantageous because it reveals the identitiy of bacteria. The 16SrRNA gene as molecular characteristic have been developed to be a useful marker molecular ofprocaryote for systematics. Identification of bacteria by 16S rRNA gene sequencing is considered tobe more accurate than phenotypic characteristics. In conclusion, the sequence analysis of 16S rRNAproved to be a useful molecular data for identification new strain of pathogenic bacteria. The isolate was identifiedas Bacillus cereus strain C4 after 16S rRNA gene sequencing and alignment by BLAST. Keywords : NA, 16S rRNA, Bacillus cereus, phylogenetic study